Pengaruh Metode Kangaroo Mother Care Terhadap Tanda-Tanda Vital, Refleks Hisap Dan Berat Badan Bayi Prematur - Nurindah Wahyuni; Tuti Seniwati; Mulhaeriah Mulhaeriah (Jurnal Kesehatan Panca Bhakti Lampung (JKPBL), 2021)
ABSTRACT Introduction: premature birth is leading cause of infant death. Kangaroo Mother Care (KMC) is one of the most effective treatments for premature infants. Aims: The purpose of this study was to investigate the effect of kangaroo Mother Care Method on vital signs, Sucking Reflexes, and Weight of Premature Infants. Method: this study was pre-experimental one grop pre and post design. The technique of sampling using concecutive sampling technique, with a large sample of 12 people. Result: the results of this study obtained vital signs (temperature, respiration, pulse), sucking reflex and infant weight increased before and after KMC, where temperature, respiration and pulse have p value = 0.001 (α = 0.05) sucking reflex p value = 0.139 (α = 0.05), infant weight p value = 0.001 (α = 0.05). Conclusions: there is the influence of vital signs and premature birth weigh before and after KMC. But, KMC has not effect on sucking reflex. Advistable for health workers to advise KMC conseling and training to the community so they can know the benefits and function of KMC in taking care of premature infants.